Strategi Naratif Dalam Iklan Online: Menganalisa Pengaruh Introducing Jo & Jek Terhadap Sikap Penonton di Platform Youtube - Carlos Pingsen Pratama; Vincent So; Sunoto; Muhammad Hafiz Ivan Irawan; Jenifer Lim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Currently, narrative online advertising is considered effective because it can shape consumer attitudes through beliefs, feelings (affect) and behavioral intentions. Narrative-style ads are in focus because they are able to shape consumer attitudes through interesting stories and provide useful information. The objectives of this study also include understanding how Jo&Jek's narrative ads influence viewers' perceptions of the brand. In addition, this study also revealed that demographic factors such as gender and online ad viewing habits can moderate the effects of Jo&Jek narrative commercials on viewers' attitudes, therefore the researcher took this case study using Go-Jek Indonesia's web narrative commercial titled